Enhancement of implant osseointegration by high-frequency low-magnitude loading. - Xiaolei Zhang; Antonia Torcasio; Katleen Vandamme; Toru Ogawa; G Harry van Lenthe; Ignace Naert; Joke Duyck (PLoS ONE, 2012)
Background Mechanical loading is known to play an important role in bone remodelling. This study aimed to evaluate the effect of high- and low-frequency axial loading, applied directly to the implant, on peri-implant bone healing and implant osseointegration. Methodology Titanium implants were bilaterally installed in rat tibiae. For every animal, one implant was loaded (test) while the other one was not (control). The test implants were randomly divided into 8 groups according to 4 loading regimes and 2 experimental periods (1 and 4 weeks). The loaded implants were subject to an axial displacement. Within the high- (HF, 40 Hz) or low-frequency (LF, 8 Hz) loading category, the displacements varied 2-fold and were ranked as low- or high-magnitude (LM, HM), respectively. The strain rate amplitudes were kept constant between the two frequency groups. This resulted in the following 4 loading regimes: 1) HF-LM, 40 Hz-8 µm; 2) HF-HM, 40 Hz-16 µm; 3) LF-LM, 8 Hz-41 µm; 4) LF-HM, 8 Hz-82 µm. The tissue samples were processed for resin embedding and subjected to histological and histomorphometrical analyses. Data were analyzed statistically with the significance set at p<0.05. Principal findings After loading for 4 weeks, HF-LM loading (40 Hz-8 µm) induced more bone-to-implant contact (BIC) at the level of the cortex compared to its unloaded control. No significant effect of the four loading regimes on the peri-implant bone fraction (BF) was found in the 2 experimental periods. Conclusions The stimulatory effect of immediate implant loading on bone-to-implant contact was only observed in case of high-frequency (40 Hz) low-magnitude (8 µm) loading. The applied load regimes failed to influence the peri-implant bone mass.